PERENCANAAN TEBAL PERKERASAN LENTUR JALAN RAYA DENGAN METODE SNI-1732-1989-F PADA RUAS JALAN TADULAKO LOLU KABUPATEN SIGI - Hasanuddin, Hasanuddin; Suratnan, Suratnan (Universitas Muhammadiyah Palu, 2017)
Planning the thickness of pavement structure is one part of the highway engineering case which aims to provide services for the traffic flow in providing thesense of security and comfort for the road users. The road of Tadulako street has significant prospects for economic activities, social, education and so on. The road is one access to the New Biromaru Market, The State Senior High School of Biromaru I, The Irrigation networks of Gumbasa, Bags of production infrastructure and the distribution of agricultural products, thus it requiring the further planning for development. The purpose of this study was to determine the composition and thickness of pavement layers on the road of Tadulako Street, Village of Lolu, Regency of Sigi by comparing the thickness of Asphalt Concrete (Laston) pavement structureand the thickness of the Penetration Layer (Lapen) pavement structure on the same value of CBR. The usefulness of this research is for consideration by the district governments in planning the road of Tadulako Street, Village of Lolu, Regency of Sigi development, especially for the writer himself, he will be able to plan the road pavement thickness. The method used in this research is a method of component analysis (SNI 1732-1989-F). The conclusion of this study is that the pavement structure of penetration layer (Lapen) is D1=7,5 cm D2=15 cm D3=27 cm, whereas laston is D1=5 cm D2=15 cm D3=20 cm. Penetration layer (lapen) is thicker sub base than the Asphalt Concrete (laston) but lapen cheaper than laston, caused mobilization, design and AMP production laston it was so expensive While volume only ± 730 m. Caused the writer recommends lapen more then logic at Tadulako Lolu street District Government Sigi.Keywords : Pavement Thickness Planning, Component Analysis Method, ISO-1732-1989-F